Diretrizes para um modelo de gestão pública ambiental: avaliação de padrões de consumo dos recursos naturais e destinação adequada dos resíduos no instituto biológico. - Guimarães, Luiz Fernando Vaz (Universidade Federal de São Carlos, 2015)
The environment has been the subject of several studies in almost every areas of knowledge. Thus, several studies have been published to clarify the environmental consequences of the growing impact of human actions. In the present study will address the co nsumption pattern, materials and natural resource economics, the applicability of environmental legislation and proper disposal of waste in the Biological Institute, linked to the Department of Agriculture of São Paulo State , in order to set guidelines for a public environmental management program. A diagnosis of the work already done by the institution revealed the existence of a Quality Management Program and a Waste Management Program , with specific and dependent actions o f the will of some persons. Later interviews were conducted by questionnaires assessing the environmental perception of employees. Data were analyzed qualitatively and quantitatively, showing that there is some separation and disposal of waste, especially those from laboratories; there is no control of natural resource consumption and environmental actions are specific and dependent on a few people. There is a general interest on the part of employees in environmental improvements, but for this specific sec tor to develop a widely publicized program is needed. Studies of environmental perception are important in the search of tools to design programs of environmental management. The A3P proved to be the most appropriate tool for public institution to be focus ed on public administration, be free and take into account the individual interests of employees and collaborators, when compared to ISO 14001 and Sigma Program
Guidelines for a model of public environmental management: consumption evaluation of natural resources and proper waste disposal at instituto biológico
Keywords: gestão pública; gestão ambiental; gestão pública ambiental; A3P; Projeto Sigma e ISO 14001; administração pública aspectos ambientais -Brasil; política ambiental; public management; public environmental; public environmental management; A3P; Sigma Program; ISO 14001; CIENCIAS BIOLOGICAS::ECOLOGIA